1992
DOI: 10.1007/bf00862973
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials in patients with non-neurological Wilson's disease

Abstract: In Wilson's disease neurological manifestations result from the damage in the basal ganglia, even if a widespread degeneration of the brain occurs. The few studies performed using evoked potentials with the aim of identifying subclinical dysfunction in the three major sensory pathways have never shown abnormalities in patients without neurological manifestations. To verify this observation we studied 12 patients suffering from Wilson's disease in a pre-neurological stage by using pattern visual evoked potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…Our study revealed EP abnormality in 61% patients with neurologic WD; abnormal MEP in 35.7%, ABER in 61.5%, VEP in 57% and SEP in 30.7%. In earlier studies, MEP abnormality has been reported in 39-50%, SEP in 15-69%, VEP in 5.3-75% and ABER in 8.3-92% [8][9][10][11][12][13][14][15][16][17][18][19][20]. MEP abnormality in our study correlated with MRI involvement of motor pathway in four patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our study revealed EP abnormality in 61% patients with neurologic WD; abnormal MEP in 35.7%, ABER in 61.5%, VEP in 57% and SEP in 30.7%. In earlier studies, MEP abnormality has been reported in 39-50%, SEP in 15-69%, VEP in 5.3-75% and ABER in 8.3-92% [8][9][10][11][12][13][14][15][16][17][18][19][20]. MEP abnormality in our study correlated with MRI involvement of motor pathway in four patients.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, WD presents with predominant extrapyramidal features, pyramidal dysfunction may be overshadowed by rigidity and movement disorders which can be evaluated by motor evoked potential (MEP). On Medline search with key words evoked potentials and WD, we could retrieve 45 articles; out of which multimodality evoked potentials were performed in 14 studies; majority included both hepatic and neurologic WD, six correlated evoked potential changes with magnetic resonance imaging findings and only two conducted MEP [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In this communication, we report multimodality evoked potential changes in patients with neurologic WD and correlate these with their clinical severity and MRI findings.…”
Section: Introductionmentioning
confidence: 99%
“…Es hat keine Befundkonstellation eine Spezifität, die im Einzelfall das Auftreten morphologischer bzw. Ein zumeist Fehlen pathologischer MRT-Befunde [18,21] und regelrechte elektrophysiologische Befunde bei neurologisch asymptomatischen Patienten unterstützt diesen Zusammenhang [1,10]. Auch in den Untersuchungen von Giagheddu et al [7] korrelieren abnorme MRT-Befunde nicht regelmäßig mit gestörten evozierten Potenzialen.…”
Section: Befundspektrum Der Evozierten Potenzialeunclassified